Effects of legume-cover crop rotations on soil pore characteristics and particulate organic matter distributions in Vertisol based on X-ray computed tomography - Tianyu Ding; Zichun Guo; Keke Hua; Zizhou Yu; Jiaqi Li; Yueming Chen; Zhibin Guo; Daozhong Wang; Jianli Liu; Xinhua Peng (Geoderma, 2025)
Cover crops have been used as an effective soil management practice to improve soil pore structure and promote particulate organic matter (POM) accumulation. However, the effects of different cover crop rotations on soil pore characteristics and the spatial distributions for POM remain poorly understood. This study examined the influence of five cropping systems (spring maize monoculture (M), wheat-maize rotation (WM), wheat-soybean rotation (WS), wheat-Cassia occidentalis rotation (WCo), and wheat-Cassia tora Linn. rotation (WCt)) on soil POM fractions, pore structure, and soil physical properties, and nutrient availability in a Vertisol. The results showed that, compared to M treatment, all four rotation systems significantly increased image-based porosity, 120–1000 μm porosity, pore surface area density, and connection probability (P < 0.05). The WCo and WCt treatments led to an increase in connected porosity by 207 % and 130 % (P < 0.05). They also significantly increased fresh POM by 90.4 % and 55.5 %, and total POM by 75.4 % and 52.4 %, respectively (P < 0.05). These treatments also significantly increased air permeability (Ka), relative gas diffusivity (Ds/D0), and saturated hydraulic conductivity (Ks) (P < 0.05). Strong correlations were observed between fresh POM and pore structural parameters (image-based porosity, connected porosity, 500–1000 μm porosity, hydraulic radius), as well as soil physical properties (Ks, Ka, Ds/D0). The positive feedback between pore structure and POM accumulation facilitated soil structural improvement under leguminous cover crop-based rotations (WCo, WCt). These findings suggest that integrating Cassia occidentalis and Cassia tora Linn. into rotation systems can effectively enhance soil structure and promote organic matter sequestration in Vertisols.